The synthesis and evaluation of 3-benzoylbenzofurans and their pyrazole derivatives against HIV-1 infections and cancer - Ms Sinothile Khuzwayo; Dr Mamoalosi A Selepe; Prof. Debra Mayer; Dr Ntombenhle Hlengiwe Gama (International Journal of Infectious Diseases)
Introduction: The human immunodeficiency virus-1 (HIV-1) remains one of the leading global epidemics in the world. The HIV/AIDS epidemic is particularly dominant in Eastern and Southern Africa, as is evident by the 670 000 annual new infections in this region alone, compared to 1.5 million global annual new infections (UNAIDS, 2022). HAART is an effective treatment for controlling HIV-1 infections; however, severe adverse events and the emergence of drug resistance have been major challenges (Amblard et al., 2022). Lenacapavir, a pyrazole-based drug, was FDA-approved in 2022 and has been proven to be the most potent HIV-1 inhibitor thus far (Segal-Maurer et al., 2022). Numerous experimental pyrazole compounds have demonstrated high potency against HIV-1 infections and have been shown to have minimal cytotoxicity, thus making them attractive candidates for HIV-1 treatment (Cherne et al., 2019). Methods: Novel 3-benzoylbenzofurans and pyrazole derivatives were synthesized and characterized using mass spectrometry (LC-MS and HRMS), NMR, and melting points. Our synthesis method involved methylating the 5-hydroxy group of 3-benzoylbenzofurans, which produced the intermediates from which the pyrazoles were derived. The 3-benzoylbenzofuran precursors and derivatives were assessed for cytotoxicity in TZM-bl cells and for anti-HIV-1 activities in Q23 and CAP210 pseudoviruses. The cytotoxic 3-benzoylbenzofurans were assessed against cervical cancer and hepatic cancer cells using both MTT assays and real-time cell electronic sensing (RT-CES) and for antioxidant activities using DPPH assays. Results: The methylated 3-benzoylbenzofurans were discovered to be cytotoxic in TZM-bl cells, while the pyrazole derivatives showed mild to low cytotoxicity. The most active compounds included a non-methylated (2,5-dimethoxyphenyl)(5-hydroxy-4,7-dimethyl-1-benzofuran-3-yl)methanone, a methylated benzofuran (2,5-dimethoxyphenyl)(5-methoxy-4,7-dimethyl-1-benzofuran-3-yl)methanone, and a pyrazole derivative (2-[3-(4-fluoro-2-methoxyphenyl)-1H-pyrazol-4-yl]benzene-1,4-diol) with IC50 values that were comparable to nevirapine in both Q23 and CAP210 pseudoviruses. The cytotoxic benzofurans demonstrated high potency against cervical cancer and hepatic cancer cells and were also demonstrated to be potent antioxidants using a DPPH assay. Discussion: The current study successfully synthesized 3-benzoylbenzofurans, methylated them, and finally prepared the pyrazole derivatives from the methylated 3-benzoylbenzofurans. Derivatization to pyrazole reduced the cytotoxicity of compounds as expected, fortunately maintaining their anti-HIV activities against pseudoviruses. Derivatives of pyrazoles increased the TPSA by 18.70 Å, which consequently lowed their cytotoxicity (Yukawa and Naven 2020). A flouro-pyrazole derivative was identified as the most potent inhibitor; although the mechanism has not been elucidated, it has the potential to inhibit the HIV capsid like lenacapavir (Segal-Maurer, DeJesus et al. 2022). The 3-benzoylbenzofurans demonstrated anticancer activities against a cervical cancer cell line and additionally displayed antioxidant activities. Conclusions: Together, these results demonstrate the potential of benzofurans and pyrazole derivatives for further development as antiretrovirals and anti-cancer treatment.